Profile of poisoning cases among females: A 5-year retrospective study from poison detection centre of a tertiary care hospital - Ali, Kashif; Pujar, Somashekhar S; Honnungar , Ravindra S; Jirli, Prasanna S; Koulapur , Vishal V; Azizuddin Junaidi, Khaja; Pushpa, M G (Journal of Indian Academy of Forensic Medicine, 2019)
Poisoning is a serious problem throughout the world that could be suicidal, homicidal or accidental. In India more than 50,000 people are dying every year from the exposure of poisonous compounds. In a developing country like India there is expansion of industrial and agricultural fields on a large scale which gives rise to more production of insecticides and its accessibility thereby increasing its exposure and toxicity. The objective of this study is to analyze the profile of Poisoning cases in females tested in Poison Detection Centre of a tertiary care hospital over a period of 5 years. It is a retrospective record-based study of all poisoning samples of females sent for analyzing to Poison Detection Centre (PDC) of KLE hospital, Belagavi from January 2012 to December 2016. The data regarding pattern of poisoning, age, occupation and basic demographics were collected from hospital records.The study included total 380 female cases of which 334 were positive for various poisonous compounds and 46 were negative for standards tested. The commonest age group was 19-29 years. Organophosphorus was commonest compound and least was Amitraz. The maximum number of cases reported were among illiterate and were from rural background involved in agricultural activities. The maximum deaths were seen with Organophosphorus compound. It is the need of hour to conduct health and poison awareness programs to keep a check on increasing rate of poisoning cases.